2013
DOI: 10.1016/j.ijsu.2012.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tamoxifen citrate on postoperative intra-abdominal adhesion in a rat model

Abstract: In conclusion tamoxifen citrate seems to be useful for preventing postoperative intra-abdominal adhesions. Its effects are in a dose and time dependent manner. Further studies must be carried out to use tamoxifen for preventing intra-abdominal postoperative adhesions in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In a previous study in a rat model, it was reported that the antifibrotic effects of tmx are associated with reduced TGF‐β1 levels, which in turn is related to the reduction in postoperative adhesion in a dose‐ and time‐dependent manner (Karaca et al . ). Therefore, in the present study, we decided to use a higher dose for a longer duration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study in a rat model, it was reported that the antifibrotic effects of tmx are associated with reduced TGF‐β1 levels, which in turn is related to the reduction in postoperative adhesion in a dose‐ and time‐dependent manner (Karaca et al . ). Therefore, in the present study, we decided to use a higher dose for a longer duration.…”
Section: Discussionmentioning
confidence: 97%
“…; Karaca et al . ). High expression of TGF‐β1 is related to chronic inflammation, extracellular matrix over deposition and scar contracture of the bile duct caused by bile (Geng et al .…”
mentioning
confidence: 97%
“…Tamoxifen, a synthetic nonsteroidal anti-estrogen agent, with anti-fibrotic properties, has also been used successfully in rats. (230) The efficacy of sex hormones appears to be unpredictable and human application has been unsuccessful. (231,232) As nitric oxide (NO) participates in the inflammatory phase of adhesion formation by generating reactive oxygen species, increasing vasodilatation, and its inhibition by using methylene blue or aminoguanidine has been shown effective in experimental models.…”
Section: Inflammatory Phasementioning
confidence: 99%
“…Other formulations containing therapeutic agents have been presented as potent candidates to prevent mesh visceral adhesion in rodent models (i.e., taxomifen and sirolimus) . However, before drawing real beneficial effect, those drugs have to be validated pre‐clinically on larger animal models, taking into account their serious side‐effects.…”
Section: Anti‐adhesive Meshmentioning
confidence: 99%